Thermal treatment of common beans (Phaseolus vulgaris L.): Factors determining cooking time and its consequences for sensory and nutritional quality. Issue 4 (30th May 2021) - Wainaina, Irene; Wafula, Elizabeth; Sila, Daniel; Kyomugasho, Clare; Grauwet, Tara; Van Loey, Ann; Hendrickx, Marc
Abstract: Over the past years, the shift toward plant‐based foods has largely increased the global awareness of the nutritional importance of legumes (common beans ( Phaseolus vulgaris L.) in particular) and their potential role in sustainable food systems. Nevertheless, the many benefits of bean consumption may not be realized in large parts of the world, since long cooking time (lack of convenience) limits their utilization. This review focuses on the current insights in the cooking behavior (cookability) of common beans and the variables that have a direct and/or indirect impact on cooking time. The review includes the various methods to evaluate textural changes and the effect of cooking on sensory attributes and nutritional quality of beans. In this review, it is revealed that the factors involved in cooking time of beans are diverse and complex and thus necessitate a careful consideration of the choice of (pre)processing conditions to conveniently achieve palatability while ensuring maximum nutrient retention in beans. In order to harness the full potential of beans, there is a need for a multisectoral collaboration between breeders, processors, and nutritionists.